FACTORS AFFECTING THE CUSTOMER'S DECISION IN USING THE SERVICES OF PT. BANK MUAMALAT TBK BINJAI SERVICE BRANCH - Rizky Fatmawati; Ayu Susanti (Proceeding International Seminar of Islamic Studies, 2021)
The formulation of the problem in this study is whether the factors of religiosity, products and services influence the customer's decision to use the services of PT. Bank Muamalat Tbk Binjai Sub Branch. The results showed that based on the validity test, all statement items on the variable were declared valid, this is evidenced by all statement items having a value of rcount rtabel. The results of the reliability test showed that each variable in this study had a cronbach alpha of more than 0.6, so it can be concluded that all variables in this study were declared reliable. The results of the t test show that the variable religiosity (X1) has a significant effect on customer decisions (Y) as evidenced by tcount ttable or 2.538 2,000, product variable (X2) has a significant effect on customer decisions (Y) as evidenced by 2.829 2.000, service variable (X3) has a significant effect on customer decisions (Y) as evidenced by 2,224 2,000. The results of the F test indicate that the three independent variables affect customer decisions in using the services of PT. Bank Muamalat Tbk Binjai Sub-Branch, this is evidenced by Fcount Ftable which is 10,784 2.72. The coefficient of determination test results shows the influence of religiosity, products and services on customer decisions in using PT. Bank Muamalat Tbk Binjai Sub-Branch is 27.8% while 72.2% is influenced by other variables not examined in this study.Keywords: Religiosity, Products, Services, Customer Decisions, BMI